PERAN TA’ARUF SEBELUM PERNIKAHAN DALAM MENCEGAH PERCERAIAN DINI - Utami, Indah Mulia; Son Ashari, Winning (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
Early divorce is a serious issue in modern society that has negative impacts on individuals and families. To build a harmonious family in accordance with Islamic principles, it is important for both prospective partners to have sufficient knowledge about each other. This can be achieved through the intermediary of ta'aruf. Ta'aruf is the process of getting to know each other between prospective husband and wife conducted before marriage. The practice of ta'aruf before marriage aims to minimize the risk of divorce. This research aims to investigate the role of pre-marital ta'aruf in preventing early divorce, with a focus on a case study in the Tambang District. The research method used is qualitative with a case study approach. Data collection for this research was done through interviews. The results of this study indicate that (1) it leads to being more selective in searching for a spouse before marriage, (2) facilitates the process towards marriage and keeps one away from temptation, (3) minimizes partner mismatch, (4) serves as a means to understand the strengths and weaknesses of the prospective spouse. Ta'aruf before marriage plays an effective role as a preventive measure to reduce the rate of early divorce. This research provides an important contribution to understanding the importance of ta'aruf before marriage in the community, particularly in the Tambang District, Kampar Regency, Riau.